Analysis of Field Modulated Magnetic Gear with Halbach Permanent Magnet Array - Cao Jiayong; Sun Kaiwen; Ren Chao; Wang Jingsen (Jixie chuandong)
The field modulated magnetic gear is a kind of non- contact magnetic drive device,and the Halbach permanent magnet array is a new permanent magnet structure which contains permanent magnets with variable magnetizing directions. In order to recognize the magnetic field property and mechanical property of the field modulated magnetic gear with Halbach permanent magnetic array,the fundamental and harmonic components of the magnetization of the Halbach permanent magnetic array are expressed by Fourier expansion. By using finite element method,two magnetic gears with radial magnetization array and Halbach array are established respectively. The magnetic field and magnetic field harmonic in air gaps of two models are compared,and the torque- angle characteristics and cogging torque characteristics of the inner rotor and outer rotor of each model are studied. By contrast,the magnetic gear with Halbach array has a more smooth torque output than the magnetic gear with radial magnetization.